2008
DOI: 10.1002/adma.200701542
|View full text |Cite
|
Sign up to set email alerts
|

Nanorods as Wavelength‐Selective Absorption Centers in the Visible and Near‐Infrared Regions of the Electromagnetic Spectrum

Abstract: Nanorods embedded in polymeric capsules are used as wavelength‐selective absorption centers to trigger the opening of the capsules and release of their contents upon laser illumination. The figure illustrates that by tuning the position of the surface plasmon peak of the nanorods, the microcapsules can be made sensitive to different wavelengths of light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 60 publications
3
65
0
2
Order By: Relevance
“…Also, such an approach represents a complementary way to that using nanoparticles for delivery. [63] Remote activation of films was conducted by a near-IR laser beam which is superior to UV [64] or visible [65] excitation because of the low absorption of the tissue and cells. [60] During the experiments, an area with nanoparticles was identified in CLSM (Figures 4 a,b).…”
Section: Resultsmentioning
confidence: 99%
“…Also, such an approach represents a complementary way to that using nanoparticles for delivery. [63] Remote activation of films was conducted by a near-IR laser beam which is superior to UV [64] or visible [65] excitation because of the low absorption of the tissue and cells. [60] During the experiments, an area with nanoparticles was identified in CLSM (Figures 4 a,b).…”
Section: Resultsmentioning
confidence: 99%
“…[105] Several research groups have reported on such systems, including triggered release from a) dye-functionalized capsules by irradiation with light, [106] b) metal nanoparticle embedded metal nanoparticles by a magnetic field, [107] microwaves, [108] or ultrasound, [109][110][111] and c) noble metal (silver, gold) embedded capsules by irradiation with a focused laser beam. [106,[112][113][114][115][116][117] The latter approach in particular has been explored extensively. Gold nanoparticles (Au NP ) exhibit a surface plasmon resonance signal in the visible spectrum around 530 nm.…”
Section: Stimuli-responsive Releasementioning
confidence: 99%
“…Most interestingly, the surface plasmon resonance signal can be modulated by controlling the shape (namely, the aspect ratio) and aggregation state of the Au NP on the surface of the PMLCs, with the signal shifted into the biologically friendly infrared region above 800 nm. [118] Moreover, further fine-tuning the composition of the PMLCs allows the PMLC membrane to be made reversibly permeable by IR irradiation, thereby releasing only discrete portions of encapsulated material, without destroying the whole capsule. [116] This principle was applied to drug delivery by Skirtach et al, who demonstrated that laser-triggered opening can be performed within living cells without impairing their viability.…”
Section: Stimuli-responsive Releasementioning
confidence: 99%
“…[105] Mehrere Arbeitsgruppen berichteten über gesteuerte Freisetzungen a) aus Farbstoff-funktionalisierten Kapseln durch Bestrahlung mit Licht, [106] b) aus Kapseln, deren Hülle Metallnanopartikel enthält, durch magnetische Felder, [107] Mikrowellen [108] oder Ultraschall [109][110][111] und c) aus Kapseln, deren Hülle Edelmetalle (Silber, Gold) enthält, durch fokussierte Laserstrahlung. [106,[112][113][114][115][116][117] Besonders der letzte Ansatz wurde intensiv erforscht. Goldnanopartikel (Au NP ) weisen im sichtbaren Spektralbereich bei einer Wellenlänge von etwa 530 nm ein Oberflächenplasmonenreso-nanzsignal auf.…”
Section: Stimulierbare Freisetzungunclassified
“…Interessanterweise kann das Oberflächen-plasmonenresonanzsignal durch eine Veränderung der Form (d. h. des Seitenverhältnisses) und des Aggregationsgrads der Nanopartikel auf der Kapseloberfläche in den für biologische Systeme verträglicheren infraroten Spektralbereich mit Wellenlängen oberhalb von 800 nm verschoben werden. [118] Bei einer präzisen Einstellung der Zusammensetzung der Kapselhülle kann diese sogar reversibel durch IR-Strahlung permeabel gemacht werden, sodass die Kapsel nicht zerstört und nur ein Teil des Inhalts freigesetzt wird. [116] Die prinzipielle Eignung des Verfahrens mit Au NP für die Verabreichung von Wirkstoffen in lebenden Zellen bewiesen Skirtach et al, indem sie zeigten, dass die Laserstrahlung die Lebensfähig-keit der Zellen nicht beeinträchtigte.…”
Section: Stimulierbare Freisetzungunclassified